2017
DOI: 10.3126/jnarc.v3i1.17270
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Garden Pea Genotypes in Eastern Hills of Nepal

Abstract: Garden pea (Pisum sativum L) is an important winter legume used as fresh vegetables and other drier food products. Despite of its importance as cash crop in many parts of Nepal, much study on various aspects for enhancing production and productivity has yet to be done. Therefore, to evaluate the production performance different genotypes of garden pea in eastern hills agro-ecological conditions present experiments were carried out consecutively for two years (2015 and 2016) at Agricultural Research Station, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
6
3
0
Order By: Relevance
“…The number of pod/plant is a variable trait and this result is in agreement with the results of Lakic et al (2017).Genotypes showed the significant variation in green pod yield/plant which indicates differential response of genotypes of this character. Similar results were reported by previous researchers (Chadha et al, 2010;Khichi et al, 2017;Poudel et al, 2017). In the study of Ei-dakkak (2016), he reported the maximum (215.3 g) green pod yield/plant in genotype of pea but our study showed that the maximum (240.5 g) green pod yield/plant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The number of pod/plant is a variable trait and this result is in agreement with the results of Lakic et al (2017).Genotypes showed the significant variation in green pod yield/plant which indicates differential response of genotypes of this character. Similar results were reported by previous researchers (Chadha et al, 2010;Khichi et al, 2017;Poudel et al, 2017). In the study of Ei-dakkak (2016), he reported the maximum (215.3 g) green pod yield/plant in genotype of pea but our study showed that the maximum (240.5 g) green pod yield/plant.…”
Section: Discussionsupporting
confidence: 92%
“…Number of seed/pod is the important yield attributing characters and this showed highly significant differences among the pea genotypes. In the study of Poudel et al (2017), they reported 6 to 8 seeds/pod which is much close to this finding. Choudhary and Sharma (2004) had also reported the similar findings in the study of pea cultivars.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Garden pea (Pisum sativum L.) is a most important vegetable cash crop in Eastern hill of Nepal. Fresh green seeds, tender pods, green immature peas and dry peas have always high market demand (Poudel et al, 2017). It is an annual winter leguminous food crop having always high demand in market.…”
Section: Introductionmentioning
confidence: 99%
“…Yield is a complex character which depend on genetic and environmental factors (Singh 1990). In the past, studies were carried out in the evaluation of different pea genotypes in Nepal (Poon et al 2004, Poudel et al 2017and Luitel et al 2021, still the selection of pea genotypes with regard to powdery mildew disease and yield have not been undertaken. Therefore, the present study was conducted to select high yielding and powdery mildew resistant pea genotypes under the sub-tropical climatic condition at Dailekh, Karnali Province.…”
mentioning
confidence: 99%